PENGUASAAN KOMPETENSI PEDAGOGIK GURU TERSUPERVISI KLINIS DAN GURU TANPA SUPERVISI DI DUA SMA SWASTA DI KOTA AMBON - Kaipatty, Leinora Juliana; Loekmono, Lobby; Slameto, Slameto (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study is an experimental research with using pretest and posttest control groupÂ design. The aimed of the study were: 1). To know the differences significant of teacherâsÂ mastery of pedagogical competences between teachers clinical supervised in SMAÂ Kristen YPKPM Ammbon and non-supervised teachers in SMA Kartika XIII-I Ambon,Â 2). To determine how the the clinical supervision influenced the teachersâ mastery ofÂ pedagogical competences. The data was collected by using observation towardÂ teaching profile competence from Wasserman and Egert. Data analyzed using t testÂ comparative and linear regression analysis. The result of the study was the coefficientÂ t test was 4,184 with significant 0,001 < 0,05. It proved that there was a differenceÂ between supervision and non-supervision teachers significantly. The clinicalÂ supervision has influence about 41,9% on teachers pedagogical competences.